Student Tuition Fee Management Using Web-Based Application System - Dahlan Susilo; Muhammad Dwi Nugroho; Diyah Ruswanti (Politeknik Pertanian Negeri Samarinda, 2023)
Access to global information online is essential for an institution or group. Users who use web-based apps from their homes or other locations may meet their requirements without traveling to the designated institution. This study aims to determine if stakeholders' demands can be met by the web-based application for tuition fee management at the Islamic boarding school